Grief elaboration of a patient with a diagnosis of advanced colon adenocarcinoma: a case study - Ramírez Luna, Carmen Enriqueta; Martínez Márquez, Marcela Citlallic; Vieyra Chacón, Juan Rubén; Alcorta Garza, Adelina (UANL. Facultad de Medicina, 2014)
Objective: The term grief, from the French term grever, which means “to burden, to oppress”, can be deined as the process through which a person must go due to the loss of a loved one. We present a case of grief elaboration in a patient and his family that face a terminal illness. Clinical case: The patient is a 51-year-old man diagnosed with stage T4a N2b M1 colon adenocarcinoma. He came to the Department of Psycho-Oncology presenting depressive symptoms, marital and family issues associated with a medical condition, and work related issues. Conclusions: The patient was diagnosed with a secondary major depressive disorder episode in reaction to his medical condition. He was prescribed anti-depressive treatment, and family psychotherapy was recommended for grief elaboration.